PERAN PENDIDIKAN DALAM PERUBAHAN SOSIAL DI SDN 2 SUKADAMAI BARU - Putri, Suciani; Liza, Levi Lauren; Neli, Neli (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2024)
Education is something that is one of the keys to the success of an individual, group or nation in realizing the welfare and prosperity of its society. The purpose of this article is to find out and understand the role of education in social change. The method used by researchers is a descriptive qualitative research method that takes data from interviews, documentation and field observations. The results of this research are, the role of education in social change in schools can create a lot of interaction and character formation which is very necessary for future generations, and the technological changes that occur can make it easier for the community, teachers and students to search for information by saving a lot of time, Even searching for information can be done anywhere and at any time.